Theory of viscoelasticity - Christensen, R. M. (Dover Civil and Mechanical Engineering., 2003)
Integration of numerous theoretical developments offers a complete, consistent description of the linear theory of the viscoelastic behavior of materials. Relevant theoretical formulations are derived from a continuum mechanics viewpoint, followed by discussions of problem-solving techniques. A welcome addition to the literature.? American Scientist. 29 figures. 1982 edition.